Demodicosis: A Case Report - Roy, Chandan Kumar; Hossain, Md Shahadat; Nigar, Ismet; Khan, Rehana Razzak; Ahmed, SM Ali (Bangladesh Journal of Medical Microbiology, 2020)
Abstract not available Bangladesh J Med Microbiol 2020; 14 (1): 20-21